Os efeitos da matéria em neutrinos de supernovas - Martins , Bianca B.; Holanda, Pedro C. (Cadernos de Astronomia, 2024)
Neutrino emissions are fundamental to the formation of supernovae, however, the collapse of the stellar core and the effects of interactions between particles in this high-density environment are not completely understood. Therefore, the current work aims to study the relationship between neutrinos and supernovae due to gravitational collapse and explore how interactions between neutrinos and the environment affect their propagation. In this sense, the behavior of neutrinos in stellar matter is modeled according to plane wave and density matrix formalisms, such that the neutrino evolution equations are analytically deduced. In this way, the occurrence of Mikheyev-Smirnov-Wolfenstein (MSW) and collective effects on supernova neutrinos is evident.